THE ROLE AND ECONOMIC SIGNIFICANCE OF AGRO-BUSINESS IN A MARKET ECONOMY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This research work comprehensively examines the role of the agribusiness system in the modern market economy, its functions in ensuring economic stability, and the laws of its development. The theoretical and methodological foundations of the agribusiness system are analyzed, in particular, the value chain from the cultivation of agricultural products to their delivery to the consumer. The study scientifically substantiates the strategic importance of agribusiness in GDP growth, ensuring employment, improving the investment climate, and guaranteeing food security. Also, international experience, in particular, cluster approaches and innovative technologies in the agricultural sector of developed countries, were comparatively analyzed with the conditions of Uzbekistan. At the end of the study, practical proposals and recommendations were developed to increase the competitiveness of agribusiness entities and digitalize the industry.